Advanced small-cell ovarian carcinoma, hypercalcemic type: a challenging therapeutic entity - Rafael Caparica Bitton (Autopsy and Case Reports, 2014)
Small-cell ovarian carcinoma (SCOC) is a rare and aggressive neoplasia, predominantly affecting young women who are frequently first diagnosed with advanced stage disease. Platinum-based chemotherapy (ChT) can provide high response rates and rapidly ameliorate symptoms in this scenario. However, progression after chemotherapy usually occurs quickly, leading to high mortality rates. In addition, ChT complications, such as tumor lysis syndrome (TLS) can also occur, jeopardizing the patient’s outcome. We present a case of metastatic SCOC in a 47-year-old patient who achieved tumor response after platinum-based chemotherapy and developed TLS, from which she recovered with supportive treatment. After the second ChT cycle, she developed febrile neutropenia and died 8 weeks after the diagnosis of SCOC. Although SCOC is a chemo-sensitive tumor, short-lived responses and frequent chemotherapy complications lead to a dismal prognosis.